Mechanisms of formative assessment in the additional professional education of teachers - O. V. Temnyatkina (Obrazovanie i Nauka)
Introduction. Many studies indicate the low effectiveness of the impact of innovations on the quality of modern education. One of the reasons for this situation is the low level of the subjective position of teachers in the development of innovations in the context of advanced training programmes.It is generally recognised that the formative assessment can directly affect the process of teachers’ person-centred training that is directly related to the processes of individualisation of educational, professional and professional activities. The article presents the experience of organisational process of formative assessment of teachers in the framework of additional professional education.Aim. The present research aims to describe the mechanisms of person-centred formative assessment in additional professional education of teachers when mastering innovations.Methodology and research methods. The study was based on the methodology of the competence-based and system-activity approaches, the author’s concept of the components of activity, taking into account the principles of organising the formative assessment by P. Black & D. Wiliam, the methodology for organising feedback in the conditions of teacher training.As a means of formative assessment in the context of the implementation of the task approach, professional tasks were used to assess the level of mastery by the teacher of innovations corresponding to the competencies of the professional standard. On the basis of emotional-psychological, regulatory, social, analytical, creative components of activity and self-improvement component, the author developed the criteria for the formative assessment in the process of mastering innovative activities by teachers. The study involved 978 Russian and foreign language teachers and mathematics teachers, who participated in advanced training programmes in 2013–2018.Results and scientific novelty. The developed mechanisms of formative assessment within the framework of advanced training programmes made it possible to implement the predictive, diagnostic and corrective functions of formative assessment; reflective dialogues created conditions for the development of the subjectivity of programme participants in the field of formative assessment. The criteria for the formative assessment of the metaprofessional competencies of teachers, designed on the basis of the author’s concept, made it possible to establish a high level of the emotional and psychological component of the activity, motivation of teachers to master innovative technologies of the system-activity approach. The manifestation of analytical and creative components turned out to be at a low level: with great difficulty, trainee teachers overcame traditional approaches to lesson design, stage development activity motivation of students, design of a competence-oriented test. This analysis could be applied as the basis for building a further trajectory for teacher development.Practical significance. The presented mechanisms for organising formative assessment can be effectively used to increase the subjective position of teachers in the development of innovations.